PERAN TERAS BACA GUYUB RUKUN DALAM MEMBERDAYAKAN MASYARAKAT DUSUN JAMBON - Kurniawan, Eko; Setyowati, Risha; Gandarizki, Muh. Nur Dear (Association of Indonesian Library and Information Professionals, 2018)
Nowadays, there are many types of libraries that are developing, one of which is the community library or commonly called the Taman Baca Masyarakat (TBM). TBM is a library located around the community aims to increase reading interest to the surrounding community. TBM located in Jambon RT 29 Argosari Sedayu village Bantul, DIY is named with Teras Baca Guyub Rukun. TBM was established since 2015 until now have programs that are able to empower the surrounding community. This article was prepared using a qualitative descriptive method, in order to be explained in detail about how the role of TBM Teras Baca Guyub Rukun in empowering the community of Jambon. The purpose of this article is to inspire other libraries from the activities which are conducted by TBM Teras Baca Guyub Rukun, thereby the community can develop economically and educationally. The conclusion of this article is that the people of Jambon village get many advantages from the presence of TBM. Starting from the children began to read, the number of plants grown by children and teenagers, the youth who began to increase their creativity in growing entrepreneurial spirit, the mother of PKK and girls who began to cook, teenagers who have dared to appear in public, and the number of teenage activities as inspired by TBM by conducted garbage bank.